Lily polysaccharides alleviate colitis through the microbiota–N8-acetylspermidine–cGAS–STING signaling axis - Wu, Yuanyu; Wan, Xiaoyu; Hou, Lu; Zhang, Haolong; Wang, Jialin; Wu, Kun; Shao, Junwei; Song, Zheyu (Frontiers in Microbiology, 2025)
IntroductionWith inflammatory bowel disease (IBD) rising and current therapies limited, novel treatments are needed. Natural products are increasingly recognized as promising options for colitis. This study evaluated the therapeutic effects and mechanisms of lily polysaccharides (LP) in dextran sulfate sodium (DSS)–induced ulcerative colitis (UC).MethodsLP was administered in a DSS-induced UC model. Gut microbiota composition was profiled by sequencing, and metabolites were assessed with a focus on N8-acetylspermidine (N8AS). In vitro assays examined LP’s impact on N8AS production and intestinal barrier repair. Exogenous N8AS supplementation was tested for anti-colitic effects. Activation of the cyclic GMP–AMP synthase–stimulator of interferon genes (cGAS–STING) pathway and pro-inflammatory cytokine production were evaluated.ResultsLP significantly alleviated colitic symptoms and restored microbial homeostasis, enriching beneficial taxa such as Bacteroides. LP markedly increased N8AS levels; in vitro, LP enhanced N8AS production, and exogenous N8AS supplementation alleviated colitis. Mechanistically, both LP and N8AS inhibited cGAS–STING pathway activation, reduced pro-inflammatory cytokines, and promoted intestinal barrier repair in vitro.DiscussionLP exerts anti-colitic activity through the microbiota/N8AS/cGAS–STING axis, linking microbial regulation, metabolic modulation, and immune signaling suppression. These findings support LP as a promising natural therapeutic for UC and provide novel insights into the beneficial effects and preliminary mechanisms of N8AS.